Potensi Metarhizium anisopliae dalam Menurunkan Populasi Larva Kumbang Badak (Oryctes rhinoceros L.) pada Tanaman Kelapa Sawit - Paisal Henri Hasibuan; Siti Hardianti Wahyuni; Meiliana Friska (Journal Agro-Livestock, 2024)
This research was carried out in June 2023 – September 2023. The study was designed using a Complete Randomized Design (RAL) with 4 treatments and 10 replicates. The parameters observed in this study were the percentage of mortality and infection, changes in the behavior of O. rhinoceros larvae, the morphology of O. rhinoceros larvae that showed symptoms of being infected with M. anisopliae and tissue damage at each stage of infection symptoms caused by M. anisopliae fungi. The highest mortality occurred in the M3 treatment (Applied with M. Anisopliae fungus on 25 grams of corn media/jar) with a mortality percentage of 91% on the 20th day after application, while for the M1 and M2 treatments, there was also mortality, but it took longer. Damage to the tissue of O. rhinoceros larvae in each symptom of infection due to the treatment of entomopathogenic fungi M. anisopliae consists of attachment and penetration of fungal spores, infection and growth of mycelium in internal tissues, production of toxins fungi, degradation of hemolymph and vital organs, death and growth of external fungi and the drying and decomposition of the larval body occurs.